Hemicycla (Hemicycla) fuenterroquensis (Gastropoda: Helicoidea: Helicidae), a new species from La Palma, Canary Islands - Castro, Juan M.; Yanes, Yurena; Alonso, Maria R.; Ibáñez, Miguel (Zootaxa, 2012)
The rugged, volcanic oceanic island of La Palma (Fig. 1), with the oldest subaerial rocks dated at 1.7 Ma, is one of the youngest islands of the Atlantic Canarian Archipelago. La Palma is an elongated island with North-South orientation (about 45 km long and near 28 km wide in the northern half, then tapering towards its southernmost tip), with an area of 708 km2 and an altitude of 2426 m above sea level (a.s.l.). The island is in the second stage (“emergence and subaerial construction”) out of the six phases of the hotspot island’s life cycle (Fernández-Palacios & Whittaker, 2010). The most recent volcanic eruption occurred at the Teneguía volcano in 1971. The island exhibits a considerable range of habitats (from arid lowland shrub zones to humid highland evergreen forests) generated by high mountains that intercept the moist trade winds. This great variety of habitats has enhanced land snail radiation and speciation, so the island accommodates about 30 validly described endemic species of land snails, most of them belonging to the main genera (e. g., Napaeus Albers, 1850, Canariella Hesse, 1918, Insulivitrina Hesse, 1923) living today in the archipelago. The genus Hemicycla Swainson, 1840 is second land gastropods in terms of species richness within the Canary Islands, with about 40 known living species (Neiber et al., 2011). Only two of these Hemicycla species are present in La Palma, H. vermiplicata (Wollaston, 1878) and H. granomalleata (Wollaston, 1878) (Fig. 2 A, E), which were merely studied conchologically back in the 19th century. Moreover, Odhner (1937) mentions the presence in Santa Cruz de La Palma of H. ethelema Mabille, 1882, a species viewed as endemic to the Gran Canaria Island, in basis to three shells placed at his disposal by Count C. Strömfelt, Stockholm, and he compares these shells with those of H. granomalleata, indicating that he finds the best concordance in all essential charecteristics, but having the H. granomalleata shells finer granulation than those of H. ethelema.